2017
DOI: 10.1089/dna.2017.3818
|View full text |Cite
|
Sign up to set email alerts
|

CCR7 Mediates TGF-β1-Induced Human Malignant Glioma Invasion, Migration, and Epithelial–Mesenchymal Transition by Activating MMP2/9 Through the Nuclear Factor KappaB Signaling Pathway

Abstract: Chemokine receptor 7 (CCR7) has emerged as an inducer of invasion, migration, and epithelial-mesenchymal transition (EMT) in cancer. In this research, human malignant glioma cells were stimulated with transforming growth factor beta 1 (TGF-β1) and siCCR7. The data show that CCR7 mediates TGF-β1-induced EMT, migration, and invasion in U251 and U87 cells and that these effects of TGF-β1 were reversed by treatment with siCCR7 or a CCR7 neutralizing antibody. Importantly, the TGF-β1-mediated increase in nuclear fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 39 publications
0
15
0
Order By: Relevance
“…A few studies suggest that P188 might inhibit the NF-kB signaling pathway 41 . If validated, it would provide a clearer understanding of the interaction between P188 and NF-kB that is a known transcription factor for MMP expressions 33,42,43 . In an animal model study, Wang et al 39 demonstrated that P188 exerts neuroprotective effects by preventing MMP-mediated tight junction degradation.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies suggest that P188 might inhibit the NF-kB signaling pathway 41 . If validated, it would provide a clearer understanding of the interaction between P188 and NF-kB that is a known transcription factor for MMP expressions 33,42,43 . In an animal model study, Wang et al 39 demonstrated that P188 exerts neuroprotective effects by preventing MMP-mediated tight junction degradation.…”
Section: Discussionmentioning
confidence: 99%
“…CXCR4 silencing could suppress the invasion and adhesion potential of U87 cells and pancreatic cancer cells, and decrease the transcriptional activity of NF-κB promoter (43,52). CCR7 could activate MMP2 and MMP9 through the NF-κB signaling pathway to mediate the migration and invasion of human malignant glioma, and these biological effects could be reversed by treatment with small interfering CCR7 or a CCR7 neutralizing antibody in vitro (93). In another PNI tumor, CCA, studies showed that NF-κB signaling could be activated by the CCL5/CCR5 axis through increasing the expression of MMP2 and MMP9, thus contributing to the invasion and metastasis of tumor cells, which could be inhibited by CCL5 neutralizing antibody or CCR5 inhibitor maraviroc (94).…”
Section: Reciprocal Interaction Between Other Factors and Chemokines mentioning
confidence: 99%
“…TGF-β is a master regulator of mesenchymal transition in GBM and induces the expression of mesenchymal genes, such as N-cadherin, ZEB1, Slug and CD44 [ 17 , 36 , 37 ]. Moreover, GSEA results showed that GBMs with high-level of PBX3 were enriched for the TGF-β signaling (Additional file 3 : Figure S3).…”
Section: Resultsmentioning
confidence: 99%